575 Heart failure as the cancer for the heart: the prognostic role of the new TNM-like classification. (8th December 2021) - Severino, Paolo; Amato, Andrea D'; Mariani, Marco Valerio; Prosperi, Silvia; Fegatelli, Danilo Alunni; Pucci, Mariateresa; Angotti, Danilo; Costi, Bettina; Vestri, Annarita; Cerrato, Enrico; Casale, Paul; Mather, Paul; et al.
Abstract: Aims: Heart failure (HF) is the pandemic of the third millennium accounting for the highest mortality rate among general population, second only to lung cancer. Beside heart, HF can affect lungs and peripheral organs, such as kidney, liver, brain, erythropoiesis, leading to multiorgan dysfunction. This is similar to spread of cancer. We proposed a new staging system of HF, named HLM, analogous to TNM classification used in oncology, which refers to heart damage (H), instead of T for tumour, lung involvement (L), instead of N for lymphnodes, and malfunction (M) of peripheral organs, instead of M for metastasis. The aim of this study was a comparison of HLM score with NYHA classes, ACC/AHA stages and HF classification by left ventricular ejection fraction (LVEF), to assess the most accurate prognosis tool for HF patients, in terms of a composite endpoint of all-cause death and hospitalization. Methods and results: We performed a multicentre observational, prospective study of consecutive patients admitted for HF, or at risk for HF. All parameters for heart, lungs, and peripheral organ function were collected and examined. Each patient was classified according to HLM, NYHA, ACC/AHA scores and LVEF, at hospital admission and at discharge. The composite endpoint was all-cause death and rehospitalization; the secondary endpoints were all-cause death, cardiac death, and rehospitalization. Patients were followed up at 12 months. We enrolled 2152 patients. Among those, 1720 patients completed the 12-months follow-up. Comparing HLM with other nosologies, the area under the ROC curve (AUC) was greater for HLM score than NYHA, ACC/AHA and LVEF scores regarding the composite endpoint (HLM = 0.644; NYHA = 0.580; ACC/AHA = 0.572; EF = 0.572) and all-cause death (HLM = 0.713; NYHA = 0.596; ACC/AHA = 0.594; EF = 0.565). HLM score related AUC showed statistically significant differences compared to LVEF ( P  < 0.001), ACC-AHA ( P  < 0.001), and NYHA ( P  < 0.001) scores' AUC, in terms of all-cause death and the composite of all-cause death and rehospitalization, at 12 months follow-up. Moreover, the AIC and BIC values to predict the composite of all-cause death and rehospitalization, all-cause death, cardiac death and rehospitalization rate at 12 months follow-up were always lower for HLM model compared with the others. Conclusions: According to our results, HLM score has greater prognostic power compared to other nosologies, in terms of composite outcome, rehospitalization, and all-cause death, as well as all-cause death, cardiac death, and rehospitalization, at 12 months follow-up in HF patients. HLM score overcomes the cardiocentric view of HF and it addresses the pathophysiological mechanisms underlining heart abnormalities. Such a multivariable, holistic staging system may be used in HF patients, in order to improve clinical management and to reduce healthcare costs.